Quality Care Quotient: A Holistic Examination of Outpatient Satisfaction Through Service Excellence at the National Brain Center Hospital - Rifai, Ahmad Widad; Dwianto, Agung Surya (Program Pascasarjana STIE Amkop Makassar, 2023)
The objective of this research is to ascertain the impact of various service quality variables, namely Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy, on the level of Outpatient Patient Satisfaction at the National Brain Center Hospital. This study utilizes a quantitative methodology with a descriptive design, and surveys were administered to a sample of 100 participants using a probability sampling technique known as simple random sampling. The data were obtained from a sample of 100 outpatient individuals at the National Brain Center Hospital using distributed questionnaires. The research employed various data analysis techniques, such as testing the research instrument, assessing data validity, conducting classical assumption tests, examining autocorrelation, performing multiple linear regression analysis, analyzing the coefficient of determination, and conducting hypothesis testing. The research findings suggest that the various dimensions of service quality have a collective positive impact, accounting for 89.5% of the overall influence. The remaining percentage is influenced by additional factors that fall outside the scope of this study. Keywords: Service Quality, Patient Satisfaction.